Kosmopolitische Pioniere »Inder_innen der zweiten Generation« aus der Schweiz zwischen Assimilation, Exotik und globaler Modernessimilation, Exotik und globaler Moderne - Jain, Rohit (Kultur und soziale Praxis, 2018)
How do members of the »second generation« in the post-colonial era develop their own life plans between racism, exoticism and diaspora?